DIPLOMASI INDONESIA DALAM PENYELESIAN SENGKETA LAUT CINA SELATAN TAHUN 2012 - 2015 - Tio Rizky; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research tries to explain how the diplomacy conducted by Indonesia in the SouthChina Sea dispute resolution. Where this dispute involves many countries both within theASEAN region and outside the ASEAN region so it is feared can disrupt the stability in theregion, and impact on the interests of Indonesia.This research uses the perspective of neorealism, neorealism is a new form of realism,neorealisme more emphasis on cooperation and role of institutions - both government andnon-government institutions in international relations. This research uses diplomacy theory,soft diplomacy, and preventive diplomacy.The South China Sea dispute has been going on for more than twenty years, someways of settling have been tried both between disputed countries and internationalorganizations such as ASEAN, but still not effective. Indonesia as an ASEAN member countryand a country bordering on the South China Sea who is also a natural leader within theASEAN region realizes that a protracted dispute will have a devastating impact on the regionand the interests of Indonesia itself. Therefore, Indonesia took part in the process of settlingSouth China Sea dispute, this can be seen from the diplomacy conducted by Indonesia,namely through first track diplomacy and second track diplomacy.Keywords: South China Sea, Dispute, Diplomacy Indonesia